Working conditions and musculoskeletal disorders in teachers of the São Paulo municipal network (Research, Society and Development, 2021)
Introduction: since ancient times, professional activity has been related to health disorders associated with working conditions, arising mainly from inadequate postures and repetitive activities of different body segments. One of the most affected classes is the teacher, and new health promotion proposals are required, given the new demands of contemporary society. Objective: to analyze health-related complaints regarding teachers from the municipal network of São Paulo, during their participation in a course offered in hybrid modality, including distance learning (DL) and face-to-face meetings. Methodology: analytical and observational research. 257 teachers participated who completed 40 classes/hours of the hybrid course, divided into three face-to-face meetings and eight mandatory sets. Data from the course's online discussion forums were examined, analyzing the main complaints related to the environment, work organization and bodily disturbances reported in the documents. Results: among the 565 registered complaints, those referring to musculoskeletal disorders were the most cited (398-70.4%), followed by vocal (64-11.3%), anatomical-affected disorders (54-9.5%) and allergic complaints (49-8.6%). There were also 470 complaints related to the environment and 184 about the organization of work. Conclusion: Teachers pointed out complaints regarding the physical environment, work organization and musculoskeletal disorders, showing a work environment with negative factors, which can directly reflect on health.